Implementasi Informasi Akuntansi Manajemen dan Metode Pengukuran Kinerja terhadap penggunaan E-Klinik (study kasus pada Klinik Rahima di Kabupaten Serang-Banten) - Eny Suheny; Holilah Holilah; Mega Arum (Jurnal Akuntansi dan Pajak, 2023)
This research is motivated by the rapid development of technology and information based on IT and is increasingly widely known by the general public, starting from information media which was initially only used on paper media, now moving to computerized media. Almost all companies, organizations, institutions, hospitals and government agencies require fast, precise and accurate data and information management in improving their performance, one of which is a clinic in which there is also information management. The purpose of this study is to analyze and examine the benefits of implementing management accounting information and performance measurement methods on the use of an E-Clinic based on a computerized application system for improving operational performance and reporting Rahima's clinic. The research method uses quantitative methods, using SPPS as a data processing tool. The results of this study are the accounting information system has a positive influence on the use of e-clinic applications. The effect of using the performance measurement method has a positive effect on the application of e-clinic applications.).